HRV16 Impairs Macrophages Cytokine Response to a Secondary Bacterial Trigger - Jubrail, Jamil; Africano-Gomez, Kshanti; Herit, Floriane; Baturcam, Engin; Mayer, Gaell; Cunoosamy, Danen Mootoosamy; Kurian, Nisha; Niedergang, Florence (Frontiers in Immunology, 2018)
Human rhinovirus is frequently seen as an upper respiratory tract infection but growing evidence proves the virus can cause lower respiratory tract infections in patients with chronic inflammatory lung diseases including chronic obstructive pulmonary disease (COPD). In addition to airway epithelial cells, macrophages are crucial for regulating inflammatory responses to viral infections. However, the response of macrophages to HRV has not been analyzed in detail. We used in vitro monocyte-derived human macrophages to study the cytokine secretion of macrophages in response to the virus. Our results showed that macrophages were competent at responding to HRV, as a robust cytokine response was detected. However, after subsequent exposure to non-typeable Haemophilus influenzae (NTHi) or to LPS, HRV-treated macrophages secreted reduced levels of pro-inflammatory or regulatory cytokines. This “paralyzed” phenotype was not mimicked if the macrophages were pre-treated with LPS or CpG instead of the virus. These results begin to deepen our understanding into why patients with COPD show HRV-induced exacerbations and why they mount a defective response toward NTHi.